EVALUATION OF RECRUITMENT POLICY IMPLEMENTATION HEAD OF THE STATE HIGH SCHOOL IN BANDA ACEH - JAMALI, YUSRA (Jurnal Ilmiah Educational Management, 2016)
The ideal profile principals and berkompetan require government intervention in the form of a policy of recruiting candidates for the principal. This study focuses on the evaluation of the implementation of recruiting candidates for the head of State Senior High School (SMAN) in Banda Aceh. This study, using a qualitative approach, with the evaluation model CIPP (Context, Input, Process, and Product). The data collection covers, interviews, observation and study of the document. The results of the study are; 1) The purpose of recruiting candidates for the principal, 2) Readiness implementation of recruiting candidates. 3) Implementation of recruiting candidates for the principal's, selection of administrative and academic, education and training, and the appointment and establishment. 4) Principal as a result of recruitment professionals who met the qualifications and competence of the administration. Based on the findings of research and analysis of data, it can be concluded that the evaluation of candidate recruitment policy is based on the principal stages and mechanisms set out in the policy. However, there are still shortcomings and weaknesses, associated with the process of the administration and the readiness of candidates of principals.